Business competitiveness in the 21st century: Trends, challenges, and opportunities - Castro Ijiri, Gabriela Lizeth (2025)
The study on business competitiveness in the 21st century reviews and synthesises the academic literature to identify trends, challenges and opportunities in a complex global context. Using a descriptive and analytical methodology based on the PRISMA guidelines, 2281 articles were evaluated, of which 50 were included in the review. The research identifies key challenges, such as technological challenges and supply chain management, as well as underlying factors, such as economic slowdown, inflation and poor education systems, which particularly affect Latin America, where low productivity and lack of infrastructure limit international performance. The findings highlight the need for countries, companies and education systems to adapt their strategies to strengthen competitiveness and promote inclusive and sustainable economic growth by aligning education programmes with market needs. This work not only enhances academic understanding of the phenomenon, but also provides an essential framework for formulating effective business strategies in a constantly evolving environment.